Identification of the most important factors related to people with cancer starting a palliative care conversation: A survey study. Issue 11 (9th October 2022) - Scherrens, Anne‐Lore; Beernaert, Kim; Deliens, Luc; Lapeire, Lore; De Laat, Martine; Biebuyck, Christine; Geboes, Karen; Van Praet, Charles; Moors, Ine; Deforche, Benedicte; Cohen, Joachim
Abstract: Objective: A late conversation about palliative care needs can lead to suboptimal care in the final months/weeks of life. Insight into factors related to patients' communication about palliative care is needed. This study aims to identify the factors associated with starting/intending to start a conversation about palliative care with the physician. Methods: We performed a cross‐sectional interviewer‐administered survey among people with incurable cancer. Purposive sampling was used, taking into account theoretically relevant heterogeneity. The questionnaire was developed based on the theory of planned behavior. Uni‐ and multivariable logistic regression analyses were performed. Results: Out of 80 participants, ten (13%) started the palliative care conversation and 18 (23%) intended to do so. People holding a positive attitude towards starting/intending to start the conversation (odds ratio [OR] 4.74; 95% CI 2.35–9.54), perceiving more benefits of it (OR 2.60; 95% CI 1.37–4.96) and perceiving a positive attitude towards the behavior in family/friends (OR 2.07; 95% CI 1.26–3.41) and the physician (OR 2.19; 95% CI 1.39–3.45) were more likely to start/intend to start a palliative care conversation; people perceiving more disadvantages (OR 0.53; 95% CI 0.32–0.87) and barriers (OR 0.31; 95% CI 0.15–0.63) were less likely to do so. These factors explained 64% of the variance. Conclusions: Our findings show that psychological and perceived socio‐environmental factors, particularly patients' attitudes, are associated with starting a conversation about palliative care. Theory‐based interventions targeting these strong associations might have a high potential to empower people with cancer to take the initiative in communication about palliative care and to improve timely initiation of palliative care.